Comparative analysis of adaptive immune responses following experimental infections of cattle with bovine viral diarrhoea virus-1 and an Asiatic atypical ruminant pestivirus. Issue 30 (16th July 2018) - Riitho, Victor; Larska, Magdalena; Strong, Rebecca; La Rocca, S. Anna; Locker, Nicolas; Alenius, Stefan; Steinbach, Falko; Liu, Lihong; Uttenthal, Åse; Graham, Simon P.
Highlights: Immune responses assessed post-infection with BVDV-1 and atypical pestivirus (TKK). BVDV-1 infection did not induce cross-neutralising antibodies whereas TKK did. TKK infection also induced better cross-reactive T cell responses than BVDV-1. Need to consider the ability of BVD vaccines to protect against atypical pestivirus. Abstract: Atypical ruminant pestiviruses are closely related to the two bovine viral diarrhoea virus (BVDV) species, BVDV-1 and BVDV-2. While there is evidence of cross-protective immune responses between BVDV-1 and BVDV-2, despite antigenic differences, there is little information on the antigenic cross-reactivity with atypical ruminant pestiviruses. The aim of this study was therefore to assess the specificity of antibody and T cell responses induced by experimental infection of calves with BVDV-1 strain Ho916, Th/04_KhonKaen (TKK), an Asiatic atypical ruminant pestivirus, or co-infection with both viruses. Homologous virus neutralization was observed in sera from both single virus infected and co-infected groups, while cross-neutralization was only observed in the TKK infected group. T cell IFN-γ responses to both viruses were observed in the TKK infected animals, whereas Ho916 infected calves responded better to homologous virus. Specifically, IFN-γ responses to viral non-structural protein, NS3, were observed in all infected groups while responses to viral glycoprotein, E2, were virus-specific. Broader antigen-specific cytokine responses were observed with similar trends between inoculation groups and virus species. The limited T cell and antibody immune reactivity of Ho916 inoculated animals to TKK suggests that animals vaccinated with current BVDV-1-based vaccines may not be protected against atypical ruminant pestiviruses.